Journée d'études Médias - Project RIDPA : L'Analyse des médias dans le cadre de la Pandemie Covid 19 - Gerardo, F.; Marques, S.; Filipe, I- (Journée d'Études sur les Médias- Project RIDPA, 2022)
Press analysis conducted with news from Portuguese newspapers about the 4 fundamental axes of the RIDPA project - right to health care, right to social life, right to free movement and right to consent and civic participation